2022
DOI: 10.1073/pnas.2113874119
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vimentin is an attachment factor that facilitates SARS-CoV-2 entry into human endothelial cells

Abstract: SARS-CoV-2 entry into host cells is a crucial step for virus tropism, transmission, and pathogenesis. Angiotensin-converting enzyme 2 (ACE2) has been identified as the primary entry receptor for SARS-CoV-2; however, the possible involvement of other cellular components in the viral entry has not yet been fully elucidated. Here we describe the identification of vimentin (VIM), an intermediate filament protein widely expressed in cells of mesenchymal origin, as an important attachment factor for SARS-CoV-2 on hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(87 citation statements)
references
References 67 publications
6
81
0
Order By: Relevance
“…Several of these mediators such as TNF-α and several interleukins can further stimulate inflammatory cells such as mast cells to increase the synthesis and secretion of histamine ( Crook et al, 2021 ; Nalbandian et al, 2021 ; Raveendran et al, 2021 ). Similar to what was observed with histamine here, the circulating vimentin has also been shown to facilitate SARS-CoV-2 endothelial cell entry ( Amraei et al, 2022 ). Ours and other such studies suggest that the circulating or local levels of endogenous substances could potentiate the entry of the virus into the endothelial cells.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Several of these mediators such as TNF-α and several interleukins can further stimulate inflammatory cells such as mast cells to increase the synthesis and secretion of histamine ( Crook et al, 2021 ; Nalbandian et al, 2021 ; Raveendran et al, 2021 ). Similar to what was observed with histamine here, the circulating vimentin has also been shown to facilitate SARS-CoV-2 endothelial cell entry ( Amraei et al, 2022 ). Ours and other such studies suggest that the circulating or local levels of endogenous substances could potentiate the entry of the virus into the endothelial cells.…”
Section: Discussionsupporting
confidence: 77%
“…In opposition to the hypothesis that the virus directly infects endothelial cells, Nascimento Conde et al (2020) have shown that recombinant ACE2 was required for the virus to infect the endothelial cells ( Nascimento Conde et al, 2020 ), while other authors have argued that the expression of ACE2 in the endothelial cells might be too low to support viral entry ( McCracken et al, 2021 ). In contrast, several other groups have found that human endothelial cells do express ACE2 and that the virus likely uses several additional protein pathways to enter the endothelial cells ( Hamming et al, 2004 ; Zhang J. et al, 2020 ; Zhao et al, 2020 ; Albini et al, 2021 ; Wagner et al, 2021 ; Zhang et al, 2021 ; Amraei et al, 2022 ). In an earlier study, we too have shown that the recombinant spike protein incubated with mouse cerebral endothelial cells for 12 h not only induced ACE2 degradation but also decreased endothelial junctional protein expression, thereby affecting endothelial barrier functionality ( Raghavan et al, 2021 ).…”
Section: Discussionmentioning
confidence: 84%
“…In this context, although neither the function of ACE2 or vimentin in cilia is known, it would be interesting to study their potential involvement in SARS-CoV-2-induced cilia alterations. In the light of recent findings proposing vimentin as an attachment factor for SARS-CoV-2 89 , 90 , a positive role of this protein in the docking of the virus onto cilia, therefore contributing to cilia dysfunction, could be speculated. Nevertheless, whether exogenous extracellular vimentin can play a beneficial or deleterious role in viral invasion remains a matter of controversy 89 , 90 .…”
Section: Discussionmentioning
confidence: 96%
“…The transmembrane spike (S) glycoprotein of SARS-CoV-2 and SARS-CoV have similar affinities to bind on human angiotensin-converting enzyme 2 (ACE2) ( Walls et al, 2020 ). Interestingly, cell surface vimentin is identified as a co-receptor for binding SARS-CoV spike proteins ( Yu et al, 2016 ) and it also acts as a co-receptor for SARS-CoV-2 spike proteins ( Suprewicz et al, 2021 ; Thalla et al, 2021 ; Amraei et al, 2022 ). Recent study demonstrated that the coexpression of vimentin with ACE2 increased SARS-CoV-2 entry in HEK-293 cells, and the inhibition of vimentin expression decreased the SARS-CoV-2 infection of human endothelial cells ( Amraei et al, 2022 ).…”
Section: Vimentin Intermediate Filaments In Pathological Roles In Lun...mentioning
confidence: 99%
“…Interestingly, cell surface vimentin is identified as a co-receptor for binding SARS-CoV spike proteins ( Yu et al, 2016 ) and it also acts as a co-receptor for SARS-CoV-2 spike proteins ( Suprewicz et al, 2021 ; Thalla et al, 2021 ; Amraei et al, 2022 ). Recent study demonstrated that the coexpression of vimentin with ACE2 increased SARS-CoV-2 entry in HEK-293 cells, and the inhibition of vimentin expression decreased the SARS-CoV-2 infection of human endothelial cells ( Amraei et al, 2022 ). Treatment with anti-vimentin antibodies considerably decreased the virus infection, which shows the direct role of surface vimentin in the binding of virus spike proteins ( Yu et al, 2016 ).…”
Section: Vimentin Intermediate Filaments In Pathological Roles In Lun...mentioning
confidence: 99%